A review of common NDTs in the monitoring and preservation of historical architectural surfaces. Issue 7 (3rd October 2017) - Zendri, Elisabetta; Falchi, Laura; Izzo, Francesca C.; Morabito, Zeno M.; Driussi, Guido
ABSTRACT: This contribution deals with the application of non destructive techniques (NDTs) in the assessment and monitoring of the state of conservation of historical architectural surfaces, during and after restoration and maintenance interventions. The aim is to present the authors' direct and in-situ experience with the applications of NDTs among noteworthy real case studies in relation to selected common types of decay. Thermal imaging, ultrasonic investigation, testing for the assessment of physicochemical properties, and Raman spectroscopy were all performed in order to address, diagnose, and monitor: detachments, loss of material coherence, discoloration, superficial deposits, and rising damp and moisture in several important Italian built heritage (e.g., the Ghirlandina Tower in Modena, the Sacra of San Michele near Turin, and the Narthex of Saint Mark's Basilica in Venice).